Pathological manifestation analysis in Curvelo-MG building (International Journal of Geoscience, Engineering and Technology, 2021)
Pathologies are present in many buildings due to several factors such as lack of technical responsibility of the work, poor project execution, lack of design or use of low-quality materials. Thus, this work arose from the need to present a treatment plan for the pathological manifestations found in a building in the central region of Curvelo, located in the state of Minas Gerais, proposing solutions to mitigate them. The methodology of this article involves four stages, the first consists of a literature review, the second is a case study, where a cadastral survey of the place where the problem is found, along with the photographic record of the pathologies found. In the third stage is made the analysis of pathologies, while in the fourth and last stage is proposed the solution of the problems found, where it was decided to perform a structural reinforcement with metal plate to contain the propagation of cracks.